Stroke Mortality Outcomes in Uganda - Olum, Sam; Muyingo, Anthony; Wilson, Tony L.; Demaerschalk, Bart M.; Hoxworth, Joseph M.; Zhang, Nan; Hentz, Joseph G.; Abdallah, Amir; Kayanja, Adrian; Aguilar, Maria I.; O’Carroll, Cumara B. (Journal of Stroke and Cerebrovascular Diseases, 2021)
Background and Purpose: Stroke outcome data in Uganda is lacking. The objective of this study was to capture 30-day mortality outcomes in patients presenting with acute and subacute stroke to Mbarara Regional Referral Hospital (MRRH) in Uganda. Methods: A prospective study enrolling consecutive adults presenting to MRRH with abrupt onset of focal neurologic deficits suspicious for stroke, from August 2014 to March 2015. All patients had head computed tomography (CT) confirmation of ischemic or hemorrhagic stroke. Data was collected on mortality, morbidity, risk factors, and imaging characteristics. Results: Investigators screened 134 potential subjects and enrolled 108 patients. Sixty-two percent had ischemic and 38% hemorrhagic stroke. The mean age of all patients was 62.5 (SD 17.4), and 52% were female. More patients had hypertension in the hemorrhagic stroke group than in the ischemic stroke group (53% vs. 32%, p = 0.0376). Thirty-day mortality was 38.1% (p = 0.0472), and significant risk factors were National Institutes of Health Stroke Scale (NIHSS) score, female sex, anemia, and HIV infection. A one-unit increase of the NIHSS on admission increased the risk of death at 30 days by 6%. Patients with hemorrhagic stroke had statistically higher NIHSS scores (p = 0.0408) on admission compared to patients with ischemic stroke, and also had statistically higher Modified Rankin Scale (mRS) scores at discharge (p = 0.0063), and mRS score change from baseline (p = 0.04). Conclusions: Our study highlights an overall 30-day stroke mortality of 38.1% in southwestern Uganda, and identifies NIHSS at admission, female sex, anemia, and HIV infection as predictors of mortality.
Keywords: Stroke; Cerebrovascular disorder; Cerebral infarction; Intracerebral hemorrhage; Sub-Saharan Africa; Outcomes